(untitled) (Research, Society and Development, 2021)
The objective of this work was to evaluate the efficiency of sanitizers sodium hypochlorite (NaClO), hydrogen peroxide (H2O2) and sodium dichloroisocyanurate (NaDCC) in microbial reduction and their influence on the sensory quality of minimally processed pitaya of the cerrado, stored at 6±1ºC for 15 days. The pitayas (Selenicereus setaceus) were previously selected, washed and sanitized with NaClO 50 and 100 mg.L-1, H2O2 3% and 6% and NaDCC 50 and 100 mg.L-1, for 15 minutes. The unsanified fruits were considered as control. Then, the fruits were cut transversely and peeled, so that the pulp was presented in halves. Then, the minimally processed pitayas were packaged in polypropylene packages wrapped in 15 µm polyvinyl chloride (PVC) for 15 days at 6±1ºC and the analyzes performed every 3 days. Coliform counts at 35ºC and 45ºC and presence of Salmonella sp. were not observed in any of the samples analyzed throughout the storage period. Sanitizers were statistically similar during storage, with a microbial reduction in the order of 1.07 log CFU.g-1 for filamentous fungi and yeast and psychrotrophic aerobic microorganisms in relation to the control. Sensory analysis showed that the minimally processed pitaya was not influenced by sanitizers, showing a gradual reduction in its grades with storage time, resulting in a shelf life of 11 days, based on grades greater than 5 ("neither liked/disliked ) for overall look, taste and impression and greater than 3 (“don’t know”) for purchase intent.